DEVELOPMENT OF INTERDISCIPLINARY ISLANDS OF RATIONALITY IN INITIAL TEACHER EDUCATION (Fiep Bulletin - online, 2017)
The objective of this article is to suggest a proposal for development of Interdisciplinary Islands of Rationality (IIR) as ateaching strategy to promote students autonomy in initial teacher education, through issues related to social context. Themethodology consisted in describing all eight steps of the IIR, proposed by Fourez (2005), with the corresponding activitiesformulated in this proposal to development in initial teacher education's classes, where the professor plans the educacional goals.Particular emphasis on preliminary stage to explore the problem situation experienced by the students, carried out throughstratificaion of categories in MAXqda10® program. It is expected the contribution of the proposed IIR to the pedagogical practice,aiming the construction of meanings on teaching and learning process in different educational areas, from deconstruction of limitedvisions, transcending the universe involved.